Strategic Planning for Slum Settlement Management in Meranti Pandak Village - Shinta Dwi Oktaviani; Ridwan Manda Putra; Indra Suandy (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
This study aimed to assess the level of slum settlement conditions and formulate appropriate management strategies for the Meranti Pandak Urban Village, Pekanbaru, Indonesia. A quantitative approach was employed using field observations, questionnaires, interviews, and secondary data collected from August to December 2024. The study area covered 384 hectares with a population of 13,642 residents, 4,426 housing units, and 2,789 households. A total of 96 respondents were selected through purposive sampling. Slum conditions were evaluated using the criteria established in the Regulation of the Minister of Public Works and Housing Number 2 of 2018, while strategic recommendations were developed through SWOT analysis supported by Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The results identified 425 households distributed across ten RTs within seven RWs as slum settlement locations. The assessment produced a total slum score of 32, classifying the area as a light slum settlement. The highest contributing factors were inadequate solid waste management (score = 13), lack of fire protection facilities (score = 10), and poor wastewater management (score = 6), whereas building conditions and clean water provision showed relatively good performance. SWOT analysis generated an IFAS score of 1.98 and an EFAS score of 2.65, showing that external opportunities exerted a stronger influence than internal conditions. The strategic coordinates of (0.28, 0.87) suggested that settlement improvement efforts should prioritize infrastructure upgrading, environmental management enhancement, community empowerment, and inter-agency collaboration.